Antimicrobial Effect of Thymus capitatus and Citrus limon var. pompia as Raw Extracts and Nanovesicles - Roberto Pinna; Enrica Filigheddu; Claudia Juliano; Alessandra Palmieri; Maria Manconi; Guy D'hallewin; Giacomo Petretto; Margherita Maioli; Carla Caddeo; Maria Letizia Manca; Giuliana Solinas; Antonella Bortone; et al. (MDPI AG, 2019)
In view of the increasing interest in natural antimicrobial molecules, this study screened the ability of Thymus capitatus (TC) essential oil and Citrus limon var. pompia (CLP) extract as raw extracts or incorporated in vesicular nanocarriers against Streptococcus mutans and Candida albicans. After fingerprint, TC or CLP were mixed with lecithin and water to produce liposomes, or different ratios of water/glycerol or water/propylene glycol (PG) to produce glycerosomes and penetration enhancer vesicles (PEVs), respectively. Neither the raw extracts nor the nanovesicles showed cytotoxicity against human gingival fibroblasts at all the concentrations tested (1, 10, 100 μg/mL). The disc diffusion method, MIC-MBC/MFC, time-kill assay, and transmission electron microscopy (TEM) demonstrated the highest antimicrobial potential of TC against S. mutans and C. albicans. The very high presence of the phenol, carvacrol, in TC (90.1%) could explain the lethal effect against the yeast, killing up to 70% of Candida and not just arresting its growth. CLP, rich in polyphenols, acted in a similar way to TC in reducing S. mutans, while the data showed a fungistatic rather than a fungicidal activity. The phospholipid vesicles behaved similarly, suggesting that the transported extract was not the only factor to be considered in the outcomes, but also their components had an important role. Even if other investigations are necessary, TC and CLP incorporated in nanocarriers could be a promising and safe antimicrobial in caries prevention.